The issue of legitimacy of political power in the conditions of the participation institutionalization - Sargsyan, Arnak (YSU Journal of International Affairs, 2021)
The article examines the issue of the legitimacy of political power and argues that legitimacy is presented as an expression of faith, it stems from citizens’ belief that the activities of political institutions are justified. Based on the above, it should be noted that there is no country in the world where the existing government is completely legitimate for the entire population. Legitimacy can never reach the level of unanimous recognition, because different groups and individuals do not equally recognize the authority of political power. Apparently, legitimacy and the ability to govern are equally important, because the crisis of legitimacy is a situation in which distrust of political institutions calls into question their existence.